Manajemen Pembelajaran Berbasis Moderasi Beragama di MTs Nurul Jadid Bali - Rofiqi (CV Narasi Khatulistiwa Indonesia, 2025)
This study aims to describe and analyze the management of learning based on religious moderation at MTs Nurul Jadid Bali, an Islamic educational institution situated in a multicultural society. The research employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The informants consist of the principal, teachers, and students. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the implementation of learning management based on religious moderation at MTs Nurul Jadid Bali is effectively carried out through three main stages: planning, implementation, and evaluation. In the planning stage, the school integrates the values of tawasuth (moderation), tasamuh (tolerance), tawazun (balance), and i’tidal (justice) into its curriculum and lesson plans. During implementation, teachers apply active, collaborative, and contextual learning methods that foster tolerant and empathetic attitudes toward diversity. The evaluation process covers cognitive, affective, and social aspects to assess students’ development of moderate character. The study concludes that learning management based on religious moderation creates a religious, inclusive, and peaceful educational environment. This model can serve as a reference for other Islamic educational institutions, especially those in multicultural areas, to develop a learning system that promotes national values and interfaith tolerance